Oil-oxidizing microorganisms, perspective for purification of the marine environment (Eurasian Journal of Ecology, 2016)
Active strains of bacteria, effectively utilized the oil from the fields of the Caspian region, isolated and selected from oilcontaminated water and sediments of the Caspian Sea. Their culture-morphological and physiological and biochemical features are studied, on this basis species affiliation is determined. The most active associations created on the basis of selected strains of oil- oxidizing microorganisms utilized 84,1-89% of oil at its 10%-rated content in the medium.
Keywords: the Caspian Sea; oil-contaminated water; sediments; oil-oxidizing microorganisms; destruction; bioremediation